Strategy for Developing the Achievement of UKM Badminton Athletes Sekolah Tinggi Olahraga and Kesehatan (STOK) Bina Guna - Dingkar Likeme Harefa; Eka Abdurrahman; Dwi Anggraini Tanjung (Journal Physical Health Recreation (JPHR), 2023)
This research aims to: 1) find out what the pattern of coaching is given to athletes who take part in training, 2) find out what are the supporting and inhibiting factors for coaching achievement in Badminton UKM STOK Bina Guna. The design of this research is qualitative research with descriptive methods. Data collection techniques are carried out by means of observation, interviews, documentation. The key instrument in this research is the researcher himself and is assisted by supporting instruments in the form of a cellphone, blank notes. The steps to analyze data are data reduction, data presentation. The results of this research are 1) Strength owned by Badminton UKM STOK Bina Guna This function is for athletes who excel, 2) Weaknesses they have Badminton UKM STOK Bina Guna The point of this is the lack of getting attention so Badminton UKM STOK Bina Guna This area still experiences deficiencies in facilities and infrastructure such as heavy training equipment, 3) Opportunities that exist in Badminton UKM STOK Bina Guna Bina is an association of badminton athletes who are highly regarded in Badminton UKM STOK Bina Guna especially if you have been at a district/city or provincial level event, 4) Positive threats can motivate athletes and coaches to improve their training performance in Badminton UKM STOK Bina Guna This benefit, while the negative threat is the low level of support from the government and for athletes who are still in school, their training time is very minimal, because there are athletes whose schools have just implemented a full day school system.